Performance and jump-to-jump development in the first female ski flying competition in history - Elfmark, O.; Sandbakk, Ø.; Brevig, M.; Ettema, G. (Frontiers in Sports and Active Living, 2024)
In 2023, for the first time in history, the international ski and snowboard federation (FIS) arranged an official ski flying competition where the 15 highest ranked women were allowed to participate. This study investigated jump-to-jump performance development in female ski flying, with men`s results used as reference data. Official FIS data from all six jumps of women were evaluated together with the eight jumps by men. Performance was evaluated by a score, where the distance points compensated by wind were divided by take-off speed, enabling performance to be evaluated across jumps and sexes. Women improved performance by 96% from the first to the sixth jump, with two major leaps; from the first to the second jump and from the first to the second day. In contrast, men mainly improved from training to competition. The best women had performance scores equivalent to the 10-20 best ranked men and the sex-difference between the top 3 athletes was 26.2%. This difference was thereafter compared to similar results in the normal and large hill World championship in Planica 2023, in which sex-differences between the top 3 were 8.6% and 14.6% in normal and large hill. This historical competition showed the importance of gaining practical experience with ski flying on performance, exemplified by the large improvement of female athletes. This, together with the enlarge sex-differences in large compared to normal hills, indicates that female ski jumpers have a particularly large improvement-potential in ski flying and must gain specific experience on this through traning and competitions.